2018
DOI: 10.1016/j.bjorl.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific quality of life after septoplasty and bilateral inferior turbinate outfracture in patients with nasal obstruction

Abstract: Septoplasty with bilateral outfracture of the inferior turbinate has proven to significantly improve disease-specific quality-of-life and this favorable outcome seems to occur precociously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The mean postoperative score reflected mild symptoms on NOSE score scale, although it remained higher than the mean score of the control group, suggesting that nasal septoplasty resulted in improved disease-specific quality of life. This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction 10,16–19. Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean postoperative score reflected mild symptoms on NOSE score scale, although it remained higher than the mean score of the control group, suggesting that nasal septoplasty resulted in improved disease-specific quality of life. This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction 10,16–19. Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous studies reporting significant reductions in NOSE scores and improvements in disease-specific quality of life after nasal septoplasty with or without turbinate reduction. 10 , 16 19 Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively. The mean preoperative and 3- and 7-month postoperative NOSE scores were 60.3±20.4, 32.9±16.8, and 39.6±33.2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Resende et al, in their study evaluating bilateral lower conchal outfracture procedure together with septoplasty, reported a preoperative mean NOSE score of 74.8 and postoperative NOSE scores of 28.3 and 21.4 at the 1-and 3-month follow-ups, respectively, which were clinically meaningful. 17 In our study population of patients with nasal obstruction, the mean NOSE score was 83.4 (83.41±8.15), whose anterior rhinoscopic examination and endoscopic evaluation revealed the cause of nasal obstruction to be septal deviation; paranasal sinus CT revealed no other pathology associated with the obstruction. Septoplasty together with radiofrequency to decrease the volume of inferior conchal hypertrophy was applied.…”
Section: Discussionmentioning
confidence: 67%
“…NOSE: Nasal obstruction symptom evaluation scale. 6,17 Over the past month, how much of a problem were the following conditions for you?…”
Section: Resultsmentioning
confidence: 99%
“…10,11 A septoplastia e a turbinectomia contribuem para melhorar a qualidade de vida em pacientes com obstrução nasal, associação já apontada na literatura. 12,13,14 Métodos subjetivos de avaliação constituem formas de demonstrar tal conjectura, como questionários. O questionário NOSE (Nasal Obstruction Sympton Evaluation) destaca-se como um instrumento utilizado antes e depois do ato operatório a fim de comparar a gravidade dos sintomas.…”
Section: Introductionunclassified